An evaluation of intervention system for addicted children in Turkey - Certel, Nurgül (Argumentum, 2016)
Drug addiction in children is an important issue in terms of the reasons and results of starting to use drugs as well as intervention methods. Drug addict children need to be assessed in their own system and studies should point to decreased age of addiction. Apparently, vast majority of studies on drug addiction are based on psychiatric studies. However, it needs to be evaluated from different perspectives that take into account complexity and diversity of children’s experiences on taking drugs and being addicted.